A Case–Control Study of the Effects of Chimarrão (Ilex paraguariensis) and Coffee on Parkinson's Disease - Medeiros, Márcio Schneider; Schumacher-Schuh, Artur Francisco; Altmann, Vivian; Rieder, Carlos Roberto de Mello (Frontiers in Neurology, 2021)
Introduction: Coffee has been inversely associated with Parkinson's disease (PD) in many studies, and caffeine is the leading candidate to mediate this effect. Mate (Ilex paraguariensis, IP), a caffeinated beverage rich in antioxidants consumed in South America, was also inversely associated with PD in one study from Argentina. Other varieties of IP infusion, such as chimarrão, were never studied in PD. Chimarrão is a common caffeinated beverage consumed in Brazil made with the leaves and stems of IP. Methods: A case–control study was conducted to evaluate the relationship between chimarrão ingestion and PD in southern Brazil. All subjects answered a questionnaire about the frequency of chimarrão and coffee intake. A multiple regression analysis adjusted for age and sex was performed to assess the association between PD and chimarrão consumption. Results: We included 200 PD patients and 200 healthy controls. High consumption of chimarrão was inversely associated with PD (OR = 0.44, 95% CI = 0.24–0.81, P = 0.008). High consumption of coffee was also inversely associated with PD, as expected. Chimarrão remained associated when adjusted for coffee consumption, smoking history, and age (OR 0.46, 95% CI = 0.25–0.86, P = 0.014). These two exposures showed an additive effect. Conclusion:Chimarrão consumption was inversely associated with PD, even after adjusting for coffee intake, suggesting a possible protective role. IP's effect can be mediated by caffeine and through its antioxidant components. Chimarrão has a lower concentration of caffeine compared with coffee and has numerous substances with antioxidative effects that may be important to PD protection. Further studies are needed to test this hypothesis.